2016
DOI: 10.1039/c5tb02035b
|View full text |Cite|
|
Sign up to set email alerts
|

Functionalised type-I collagen as a hydrogel building block for bio-orthogonal tissue engineering applications

Abstract: In this study, we derivatized type I collagen without altering its triple helical conformation to allow for facile hydrogel formation via Micheal addition of thiols to methacrylates without the addition of other crosslinking agents. This method provides the flexibility needed for fabrication of injectable hydrogels or pre-fabricated implantable scaffolds, using the same components by tuning the modulus from Pa to kPa. Enzymatic degradability of the hydrogels can be also easily fine tuned by variation of the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 53 publications
5
67
0
1
Order By: Relevance
“…41 Hydrogel stability is an important factor to determine whether photochemical crosslinking can aid in slowing down the enzymatic degradation of collagen hydrogels once implanted in vivo. 31,42 Results from the degradation study are in agreement with a previous study that showed that CMA hydrogels photochemically crosslinked with I2959 degraded significantly slower compared to uncrosslinked hydrogels. 27 Specifically, the residual mass of photochemically crosslinked hydrogels was reported to be around 60% at 3 h which is comparable to the results observed in the current study [ Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…41 Hydrogel stability is an important factor to determine whether photochemical crosslinking can aid in slowing down the enzymatic degradation of collagen hydrogels once implanted in vivo. 31,42 Results from the degradation study are in agreement with a previous study that showed that CMA hydrogels photochemically crosslinked with I2959 degraded significantly slower compared to uncrosslinked hydrogels. 27 Specifically, the residual mass of photochemically crosslinked hydrogels was reported to be around 60% at 3 h which is comparable to the results observed in the current study [ Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Hydrogel stability is an important factor to determine whether photochemical crosslinking can aid in slowing down the enzymatic degradation of collagen hydrogels once implanted in vivo . Results from the degradation study are in agreement with a previous study that showed that CMA hydrogels photochemically crosslinked with I2959 degraded significantly slower compared to uncrosslinked hydrogels .…”
Section: Discussionsupporting
confidence: 88%
“…The bio-ink is emerged as the use of ink-jet printing, including polymer and hydrogel for scaffolds, growth factors, cells in tissue engineering. In this review, we focus the hydrogel for scaffold (10), capable to provide cellular microenvironment (11,12) and building blocks for 3D bio-printing (13). The hydrogels are the polymeric materials derived from naturally or synthetically, capable of embedding water in their three-dimensional network.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels can e.g. be covalently crosslinked by click-reaction between thiols and methacrylated collagen [76] or methacrylated hyaluronic acid [77]. Physically crosslinked hydrogels rely on supramolecular connections such as electrostatic-or hydrophobic interactions, and hydrogen bonding.…”
Section: Hydrogels To Mimic the Ecm For Cell Supportmentioning
confidence: 99%